Dance and Parkinson's: A review and exploration of the role of cognitive representations of action. (February 2020) - Bek, Judith; Arakaki, Aline I.; Lawrence, Adam; Sullivan, Matthew; Ganapathy, Gayathri; Poliakoff, Ellen
Highlights: Dance can provide both motor and non-motor benefits in Parkinson's disease (PD). Dance utilises internal action representations through observation and imagery. Music promotes and supports action representation in dance. Action representation may contribute to positive effects of dance for PD. Future research should explore mechanisms of action representation in dance for PD. Abstract: Parkinson's disease (PD) is a neurodegenerative condition that causes both sensorimotor and non-motor impairments, and there is a clear need for non-medical approaches to improve quality of life. Dance is an increasingly popular activity among people with PD, which demonstrates potential therapeutic benefits. However, findings to date have been inconsistent, and little is known about the mechanisms underlying benefits of dance in PD. In this review, we provide an overview of research into dance for people with PD. The majority of quantitative evidence is in the sensorimotor domain, but cognitive, psychological and social effects have also been reported. We consider the role of cognitive representations of action within dance through observation, imitation and imagery, which may contribute to both sensorimotor and non-motor outcomes for people with PD. Moreover, we discuss how these processes may be enhanced through dance to provide further benefits in everyday life. Finally, we propose avenues for future research to increase understanding of action representation in dance for PD, which has the potential to inform practice and maximize benefits.